2014
DOI: 10.1159/000358701
|View full text |Cite
|
Sign up to set email alerts
|

MiR-16 Induced the Suppression of Cell Apoptosis While Promote Proliferation in Esophageal Squamous Cell Carcinoma

Abstract: Background/Aims: MicroRNAs (miRNAs) are non-coding small RNAs that regulate cell proliferation and functions by interfering with the translation of target mRNAs. Altered expression of miRNA is known to induce various human malignancies, but little is known about the role of miRNAs in esophageal squamous cell carcinoma (ESCC). Methods: RT-PCR and Western blot were used to examine the expression of miRNAs and candidate genes in 40 pairs of squamous cell carcinoma of human. MiR-16 mimics and inhibitor were transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…Specifically for EC, it is already reported that miRNAs contributes to proliferation and invasion [19,20]. MiR-16 induced the suppression of cell apoptosis while promote proliferation in esophageal squamous cell carcinoma [21]. miR-625 down-regulation promotes proliferation and invasion in esophageal cancer by targeting Sox2 [22].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically for EC, it is already reported that miRNAs contributes to proliferation and invasion [19,20]. MiR-16 induced the suppression of cell apoptosis while promote proliferation in esophageal squamous cell carcinoma [21]. miR-625 down-regulation promotes proliferation and invasion in esophageal cancer by targeting Sox2 [22].…”
Section: Discussionmentioning
confidence: 99%
“…ESCC is the predominant cause of esophageal cancer being responsible for approximately 60-70% of all cases of esophageal cancer worldwide, while EAC accounts for 20-30%, and a number of less common types also occur. However, the incidence of EAC is steadily increasing [7,8]. Any factor which causes chronic irritation and inflammation increases the risk of ESCC, and tobacco and alcohol consumption are therefore well established as the primary risk factors for ESCC [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that miRNAs are dysregulated in various cancers, and that their expression is relevant to a diverse array of tumors [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%